Pengaruh Kompensasi, Motivasi, Kinerja, dan Budaya Perusahaan Terhadap Turnover Karyawan PT Solid Gold Berjangka - Asya Astie Anggi Anie; Cikal Nur Padila; Salsabilah Risangayu; Fadhilla Prasastya Khansa (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study aims to determine the effect of compensation, motivation, performance, and corporate culture on employee turnover at PT Solid Gold Berjangka. This study uses a quantitative method with a sampling technique that is random sampling technique to employees of PT Solid Gold Futures. The research instrument is using a questionnaire. Based on the distribution of questionnaires, the total respondents obtained are as many as 102 respondents. The results of the respondents were analyzed with validity tests, reliability tests, classical assumption tests, and hypothesis testing using the SPSS 26 program. has an effect on employee turnover, performance has an effect on employee turnover, and Corporate Culture has an effect on employee turnover.